Effect of natural ventilation on airborne disease infection risk in lecture halls - Souza, Pedro Carmo e (2024)
This dissertation shows that two calibration indices suggested by ASHRAE to calibrate energy and water demand simulations can be used to calibrate any type of simulation, including natural ventilation. The authors subsequently use these indices to create a calibrated simulation model of a three-story, 30-classroom lecture hall in tropical climate, and by virtue of assessing the air renovation profile of each of its classrooms, also create an airborne disease infection risk matrix for that building, which can be adapted to similar lecture halls. The risk matrix accounts for three different diseases’ quanta emission rates, three different occupation rates (10%, 50% and 90% occupation) and classroom permanence times of up to 250 minutes. Findings suggest ventilation chimney height to be more influential to air renovations than temperature difference alone, that higher occupation rates resulted in more air renovations per hour, but also in higher infection risk, and that differently from temperate climate research has shown, tropical classrooms equipped with thermal chimneys can rely on natural ventilation to reduce airborne infection risk to an acceptable threshold. Keywords: COVID-19. Building Energy Simulation. Measles. Tropical climate. Thermal Chimney.